Recent advances of natural biopolymeric culture scaffold: synthesis and modification. Issue 2 (1st February 2022) - Yap, Jia Xin; Leo, C.P.; Mohd Yasin, Nazlina Haiza; Show, Pau Loke; Chu, Dinh-Toi; Singh, Vijai; Derek, C.J.C.
ABSTRACT: Traditionally existing 2D culture scaffold has been inappropriately validated due to the failure in generating the precise therapeutic response. Therefore, this leads to the fabrication of 3D culture scaffold resolving the limitations in the in vivo environment. In recent years, tissue engineering played an important role in the field of bio-medical engineering. Biopolymer material, a novel natural material with excellent properties of nontoxic and biodegradable merits can be served as culture scaffold. This review summarizes the modifications of natural biopolymeric culture scaffold with different crosslinkers and their application. In addition, this review provides the recent progress of natural biopolymeric culture scaffold mainly focusing on their properties, synthesizing and modification and application.